Didattica generale e valutazione espansa: aspetti epistemologici e metodologici - Franceschini, Giuliano (Studi sulla Formazione/Open Journal of Education, 2017)
The article describes three approaches to scholastic evaluation: docimological, formative and organizational. The aim is to link the various forms of evaluation to the curriculum building from the point of view of general teaching, with particular attention to the methodological and epistemological aspects.